Effect of playing methods on the Dribble Ability of the Football Game - Alan Alfiansyah Putra Karo Karo; Benny Aprial M; Ika Endah Puspita Sari; Hardodi Sihombing; Liliana Puspa Sari (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2020)
This research was motivated by the low level of dribble skills in the game of football in class VIII students of Budi Agung Private Junior High School, Medan. Based on this, the research objective was to determine the effect of playing methods on the dribbling ability of soccer games. The population and sample studied in this study were 30 students and the sample was taken using total sampling. This research is a field experiment research and the design of this study used a pre test post test group design. From the research results, it can be seen that the significance (0.010) is smaller than 0.05 and the t-test result (2.739) is greater than the t-table (0.3610), so it can be concluded that there is a significant effect of the playing method on the dribble ability of the game. football students of class VIII SMP Private Budi Agung Medan.